Analisis Pengaruh Belanja Pemerintah, Pengangguran Dan Inflasi Terhadap Kemiskinan Di Provinsi Sumatera Utara - Rifka Aqiila Nasution; Sarma Juliana Silaban; Zaskya Humairah (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This study aims to determine and analyze the effect of government spending, unemployment and inflation on poverty in North Sumatra Province. This study uses secondary data taken from the BPS of North Sumatra Province for the observation years 1991-2020. This study uses multiple linear regression analysis with the ordinary least squares (OLS) method. The assumption test used is the normality test, autocorrelation test, multicollinearity and heteroscedasticity test. The results of this study examine the partial effect, simultaneous effect and the coefficient of determination. All data processing in this research uses the Eviews 9 analysis tool. From the results of this study it is known that: 1) Government spending has a negative and significant effect on poverty in North Sumatra Province, 2) Unemployment has a positive and significant effect on poverty in North Sumatra Province, 3) Inflation positive and significant effect on poverty in North Sumatra Province.